Idealised simulations of sting‐jet cyclones. (21st March 2013) - Baker, L. H.; Gray, S. L.; Clark, P. A.
Abstract An idealised modelling study of sting‐jet cyclones is presented. Sting jets are descending mesoscale jets that occur in some extratropical cyclones and produce localised regions of strong low‐level winds in the frontal fracture region. Moist baroclinic lifecycle (LC1) simulations are performed with modifications to produce cyclones resembling observed sting‐jet cyclones. A sting jet exists in the idealised control cyclone with similar characteristics to the sting jet in a simulation of windstorm Gudrun (a confirmed sting‐jet case). Unlike in windstorm Gudrun, a low‐level layer of strong moist static stability prohibits the descent of the strong winds from above the boundary layer to the surface in the idealised case. Conditional symmetric instability (CSI) exists in the cloud head and dissipates as the sting jet leaves the cloud head and descends. The descending, initially moist, sting‐jet trajectories consistently have negative or near‐zero saturated moist potential vorticity but moist static stability and inertial stability, consistent with CSI release; the moist static stability becomes negative during the period of most rapid descent, by which time the air is relatively dry implying conditional instability release is unlikely. Sensitivity experiments show that the existence of the sting jet is robust to changes in the initial state, and that the initial tropospheric static stability significantly impacts the descent rate of the sting jet. Inertial and conditional instability are probably being released in the experiment with the weakest initial static stability. This suggests that sting jets can arise through the release of all three instabilities associated with negative saturated moist potential vorticity. While evaporative cooling occurs along the sting‐jet trajectories, a sensitivity experiment with evaporation effects turned off shows no significant change to the wind strength or descent rate of the sting jet implying that instability release is the dominant sting‐jet driving mechanism.